EFEKTIVITAS PENGGUNAAN STRATEGI PEMBELAJARAN EKSPOSITORI BERBANTUAN MACROMEDIA FLASH 8 TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA N 1 PANYABUNGAN UTARA - rizkiani ani; Marzuki Ahmad; Januardi Rosyidi Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
ABSTRACT The aim of this study is to describe the effectiveness using expository strategy by helping macromedia flash 8 on students’ mathematical problem solving ability on topic of opportunity at the eleventh grade students of SMA Negeri 1Panyabungan Utara. This research was conducted by applying experimental (one group pre test post test design) with 24 students as the sample and they were taken by using cluster sampling technique from 49 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using expository strategy by helping macromedia flash 8 was 3.6 (very good category), (b) the average of students’ mathematical problem solving ability on topic of opportunity before using expository strategy by helping macromedia flash 8 was 53.12 (fair category) and after using expository strategy by helping macromedia flash 8 was 74.50 (good category) and (c) classical completeness showed 75% (effective category). It means, using expository strategy by helping macromedia flash 8 is effective on students’ mathematical problem solving ability on the topic opportunity at the eleventh grade students of SMA Negeri 1Panyabungan Utara. Keywords: effectiveness, strategy, expository, macromedia flash 8, problem solving